2022
DOI: 10.7759/cureus.32123
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Serum Ferritin Levels With Non-scarring Alopecia in Women

Abstract: We designed this study to evaluate the association of serum ferritin levels with non-scarring alopecia in women. MethodologyAll patients were diagnosed by performing a clinical examination of the crown part width and occiput. Ludwig's classification was used to categorize the cases into grades I-III. Different laboratory tests were performed for the baseline investigation, including serum iron, total iron-binding capacity (TIBC), hemogram, and thyroid function tests. Of the 5 ml of venous blood drawn for routi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
(14 reference statements)
2
2
0
Order By: Relevance
“…The results of our study offer further support for the theory that there is a link between low serum ferritin levels and alopecia areata. In our research, we defined low serum ferritin levels as those below 20 ng/mL, which is consistent with the lower limit of normal serum ferritin levels established in a study conducted by Muhammad Fawad et al 20 . His study also reported that the average serum ferritin level in the group with alopecia areata was 19.71 ± 18.56 mg/mL, and 65.2% of individuals in the case group had low serum ferritin 20 .…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The results of our study offer further support for the theory that there is a link between low serum ferritin levels and alopecia areata. In our research, we defined low serum ferritin levels as those below 20 ng/mL, which is consistent with the lower limit of normal serum ferritin levels established in a study conducted by Muhammad Fawad et al 20 . His study also reported that the average serum ferritin level in the group with alopecia areata was 19.71 ± 18.56 mg/mL, and 65.2% of individuals in the case group had low serum ferritin 20 .…”
Section: Discussionsupporting
confidence: 84%
“…In our research, we defined low serum ferritin levels as those below 20 ng/mL, which is consistent with the lower limit of normal serum ferritin levels established in a study conducted by Muhammad Fawad et al 20 . His study also reported that the average serum ferritin level in the group with alopecia areata was 19.71 ± 18.56 mg/mL, and 65.2% of individuals in the case group had low serum ferritin 20 . These findings closely mirror the results obtained in our own study.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…About 25% of the body's iron is stored in serum ferritin, and fluctuations in these levels may impact the process of hair growth. 36 The test treatment used here restores iron levels in blood and helps in managing hair loss caused by iron deficiency. This is attributed to improved serum ferritin content by 27% post consumption of test treatment.…”
Section: Discussionmentioning
confidence: 99%